(untitled) (Academicia Globe: Inderscience Research, 2022)
This paper aims to evaluate and study the complications of patients with intracranial aneurysms, and This study consisted of two groups Ruptured Aneurysms (100 patients) and Unruptured Aneurysms (50).Approvals and licenses for this study were obtained by the relevant committees. Information and demographic data for patients were collected from different hospitals in Iraq, where this study was conducted retrospectively.The two groups were compared to found the effect of complications on patients, and we note that there is a statistical relationship between the two groups <0.001 We conclude from this study that aneurysms are pathological aneurysms in the lumen of blood vessels. The rupture of the aneurysm leads to subarachnoid hemorrhage and thus to haemorrhagic stroke.The mortality rate, in this case, is moderate, in addition to the presence of serious neurological problems.